Analisis Pemakaian Klausa Relatif Dalam Novel “Tensei Shitara Suraimu Datta Ken” Jilid I Karya Fuse - Huda Nur Rabbani; Rina Fitriana; Alo Karyati (IDEA : Jurnal Studi Jepang, 2021)
ABSTRACT: This study discusses the use of relative clauses in Fuse's novel "Tensei Shitara Suraimu datta Ken". The main focus of this thesis is the use of Japanese relative clauses based on sentence structure and the meaning contained therein. The theory used is the syntactic theory which makes phrases, clauses and sentences as the object of research and the relative clause theory of Japanese.